The Effect of Task Difficulty on the P300 Response in Children with Learning Disabilities - Shalini Arehole (Journal of All India Institute of Speech and Hearing, 1970)
The study involved assessment of P 300, an auditory event related potential in children with learning disabilities (LD). Children with LD are known to have difficulty with challenging auditory listening tasks. Specifically, when they are tested using behavioral measures, they perform poorly if the stimulus is distorted. Therefore, the objective of this study was to determine if we can observe similar findings using auditory electrophysiological measures. P-300 recordings were obtained from Children with LD using stimuli that were difficult to discriminate and compared with the recordings from children without LD. The study revealed that P 300 latencies were significantly longer and P300 amplitudes were significantly smaller under difficult task compared to standard task for both children with LD and children without LD, however, there was no significant difference between the participant groups. When the inter-peak latencies between P3-P2 were compared between Children with LD and children without LD, a significant difference was noted in the difficult task condition. Specifically, Children with LD had significantly longer P3-P2 inter peak latency compared to children without LD for thedifficult task condition. These results confirm that the strategy of stressing the auditory processing system by increasing the difficulty of the discrimination task was successful in differentiating children with LD from children without LD. However, one must use sophisticated measures such as inter-peak latency and not limit to evaluating absolute latency and amplitude of P 300 potential.